2022
DOI: 10.1002/ehf2.13913
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource use of patients with transthyretin amyloid cardiomyopathy

Abstract: Aims Transthyretin amyloid cardiomyopathy (ATTR-CM) is the cardiac manifestation of transthyretin amyloidosis (ATTR).The aim of this study was to estimate healthcare resource use for ATTR-CM patients compared with heart failure (HF) patients, in Denmark, Finland, Norway, and Sweden. Methods and results Data from nationwide healthcare registers in the four countries were used. ATTR-CM patients were defined as individuals diagnosed with amyloidosis and cardiomyopathy or HF between 2008 and 2018. Patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…The high healthcare cost of ATTR-CM compared to other types of heart failure is also in line with the findings of Lauppe et al. [ 21 ], who demonstrated higher healthcare resource use among Scandinavian ATTR-CM patients than among matched heart failure patients without ATTR-CM. The study by Lauppe et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The high healthcare cost of ATTR-CM compared to other types of heart failure is also in line with the findings of Lauppe et al. [ 21 ], who demonstrated higher healthcare resource use among Scandinavian ATTR-CM patients than among matched heart failure patients without ATTR-CM. The study by Lauppe et al.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies in Scandinavia have shown that ATTR-CM imposes a considerable burden on the healthcare system [ 21 , 22 ] with more hospitalization and outpatient visits compared to other causes of heart failure [ 21 ]. However, studies investigating healthcare resource use and costs in relation to the different stages of heart failure progression are lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 14 These delays can lead to disease progression, lack of or inappropriate treatment, and/or higher health care utilization in many patients. 28 Screening and targeted testing to enhance early diagnosis is critical, as improper or delayed diagnosis can have prognostic and therapeutic implications. Ensuring appropriate and timely diagnosis and treatment, especially in advanced disease, is paramount to allow patients to benefit from earlier access to new disease-modifying therapies.…”
Section: Discussionmentioning
confidence: 99%